Quantifying the trade effect of sanitary and phytosanitary regulations in OECD countries on South African food exports - Ngqangweni, Simphiwe Syneon (University of Pretoria, 2013)
Dissertation (MCom (Agricultural Economics))--University of Pretoria, 2005.